Exploration of demographic prevalence of mild cognitive impairment using Montreal cognitive assessment: A cross-sectional pilot study in the Cape Coast Metropolis, Ghana. - David Larbi Simpong; George Nkrumah Osei; Richeal Odarko Mills; Christopher Amaleyele Anyebem; Benjamin Kofi Aikins; Charlotte Gyanwaa Melfah; Bridget Amoanimaa Osei; Ansumana Bockarie (IBRO Neuroscience Reports)
Background: The Global prevalence of dementia is projected to rise, particularly in low and middle-income countries like Ghana. Mild cognitive impairment (MCI), an intermediate phase between normal cognitive aging and dementia, is characterized by an objective and subjective decline in cognitive abilities. Individuals with MCI have a greater likelihood of progression to dementia. Purpose: There is a paucity of studies focused on assessing the prevalence, risk factors and characteristics of mild cognitive impairment within the Ghanaian population. This study assessed the prevalence of mild cognitive impairment and explored its relationship with various sociodemographic factors. Methods: A prospective cross-sectional analytical study within Cape Coast, Ghana, evaluating the cognition of 100 participants using the Montreal Cognitive Assessment (MoCA) tool. The prevalence of MCI was determined using simple descriptive measures. The two-way ANOVA was used to determine risk factors for developing MCI. The Pearson correlation coefficient was used to determine the relationship between educational level and MoCA score. Results: A majority (65.4 %) of participants within the age group 40–49 years had mild cognitive impairment. 42.86 % of male and 40.54 % of female participants had MCI (MoCA score < 26). There was a significant correlation (r= 0.608, p= 0.0001) between the educational level of participants and the MoCA score. Participants classified as having MCI based on their MoCA score, performed significantly poorer in visuospatial, attention, language, abstraction and delayed recall domains compared to those with normal cognition. Conclusion: The MoCA tool is a useful for detecting MCI, particularly among Ghanaians with at least 7 years of formal education. The prevalence of MCI among individuals aged 40–49 years in the Cape Coast Metropolis represents an important health burden.